EFFICIENCY OF DRIP IRRIGATION IN ZHALOLLITDIN SARDOR KHAMKOR IN NAMANGAN REGION (British Journal of Global Ecology and Sustainable Development, 2023)
The article provides information on the results achieved using the drip irrigation method in the farm of Jalaluddin Sardar Hamkor of the Namangan region.